Improving scholarship accessibility with reinforcement learning - Haining Wang; Jason Clark; Hannah McKelvey; Leila Sterman; Gao Zheng; Zuoyu Tian; Xiaozhong Liu (Information Research: An International Electronic Journal)
Introduction. A vast amount of scholarly work is published daily, yet much of it remains inaccessible to the general public due to dense jargon and complex language. We introduce a reinforcement learning approach that fine-tunes a language model to rewrite scholarly abstracts into more comprehensible versions.